The Dynamics of Outsourcing: From Labor Cost-Saving to Preference-Based Outsourcing - Wan-Jung Cheng; Raymond G. Riezman; Ping Wang (Center for Economic Studies and ifo Institute (CESifo), 2020)
Ronald W. Jones (2000) celebrated book has inspired a generation of work that has been devoted to understanding the causes and consequences of outsourcing. While much of this work has focused on the outsourcing versus domestic production decision of the firm with labor cost-saving as the key driver for outsourcing, we further explore how preference-based outsourcing may arise in a dynamic world equilibrium. We address this problem in a North-South model in which the outsourcing decision depends not only on labor costs but also on information about local preferences that arise with outsourcing. As the South develops, demand for manufactured goods becomes more important, so identifying specific tastes of South consumers matters more. As a result, preference-based outsourcing displaces cost-saving outsourcing. Our quantitative analysis indicates that, as both agricultural and manufacturing technologies grow over time, the dynamic world equilibrium switches from the export regime to the cost-saving outsourcing regime, and eventually to the preference-based outsourcing regime.
Keywords: F21; F23; F43; O19; 330; dynamic outsourcing; learning and taste-matching; organizational choice